2021
DOI: 10.1016/j.pedn.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Associated Factors Among Children Aged 6–23 Months in Indonesia

Abstract: Background: Optimum feeding practice is the key to determine development and growth among infants and young children. Dietary diversity is considered an indicator to assess nutritional adequacy.Objectives: This study aimed to determine the factors that associated with minimum dietary diversity types among children aged 6-23 months in Indonesia. Methods: Secondary data analysis was carried out for this study using the Indonesian Demographic and Health Survey (IDHS) 2017. The study was conducted with inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 24 publications
12
24
1
2
Order By: Relevance
“…In our study, it was found that the likelihood of meeting the requirement for minimum dietary diversity was significantly higher among children who belonged to the 12–17 months age bracket, compared with those belonging to the 0–5 months age bracket, indicating that increased age was positively associated with minimum dietary diversity. This finding is similar to that of a past study from Indonesia [ 60 ], in which children aged 12–17 months were more likely to receive various foods with each meal than younger children. This finding should motivate health workers in India to promote the benefits of various foods, targeting mothers with younger children.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, it was found that the likelihood of meeting the requirement for minimum dietary diversity was significantly higher among children who belonged to the 12–17 months age bracket, compared with those belonging to the 0–5 months age bracket, indicating that increased age was positively associated with minimum dietary diversity. This finding is similar to that of a past study from Indonesia [ 60 ], in which children aged 12–17 months were more likely to receive various foods with each meal than younger children. This finding should motivate health workers in India to promote the benefits of various foods, targeting mothers with younger children.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with earlier studies in Indonesia (15,17) and in other low-and middle-income countries (18,24,27,28) , we found that mothers with higher educational levels tend to feed their children with a more diversified diet. Highly educated mothers might have more information and better understand educational messages, and they might also have learnt about child feeding at school (37) .…”
Section: Trends Of Minimum Dietary Diversity and Food Group Consumptionsupporting
confidence: 91%
“…This finding was consistent with studies conducted in Somalia and other studies conducted in Ethiopia [ 24 26 ]. However, it’s higher than studies conducted Nepal, Indonesia, and Tanzania [ 12 , 27 , 28 ]. The possible discrepancy is due to low food production and consumption, as well as people's purchasing capacity in Ethiopia for a variety of food goods.…”
Section: Discussionmentioning
confidence: 80%